Design understanding the elements - Strzelinski, James; Hollaender, Sherri; Roach, John (New York : Insight Media, 2007)
Featuring a professor and students from the Parsons School of Design, this program examines the elements of design. It discusses line; shape, including two- and three-dimensional, geometric, and organic; visual and tactile textures; size; and such color principles as value, hue, complimentary, analogous, triadic, additive and subtractive colors, and primary colors. Examples from fields such as architecture, fashion, interior design, and art are included
Title from title screen
DVD format
Keywords: Design; Color in design